Leading effective meetings in a hospitality organization - Slobodan Ivanovic; Vlado Galicic; Nikola Susnjar (UTMS Journal of Economics, 2010)
Today's business environment demands of the individual manager to lead effective meetings. This is a skill which has to be studied and to be used and constantly optimized in order to keep the team focused on the goals that were set. Meetings keep track of a teams and the organizations goals that are being met or not being met. The specific focus of a certain meeting depends on what on what is to be achieved, whether that be setting goals or keeping evidence of what is being done, and to do this one needs the proper information to lead it correctly and efficiently.
Keywords: 330; meetings; conflicts; leaders; meeting techniques; team resistance